GENERATION Z: IMPLICATIONS FOR UNIVERSITIES - Jacl Kalpakian; Abdelkarim Marzouk (ELite Journal : International Journal of Education, Language, and Literature, 2023)
Providing proper educational services to Gen Z students poses a serious challenge to educators worldwide. This article attempts to make sense of the literature surrounding it. Using a literature review and reflections, this paper explores the implications of Generation Z on the University. It aims to see how universities can serve this current generation of students, especially those in the Global South. The literature review covers the period ending in 2020. The paper analyzes patterns in the literature and notes differences between various countries and disciplines in their approach to the challenges posed by integrating Generation Z into universities. Using a combination of literature and reflections on the practice of education, the paper argues that Generation Z can be served in tertiary education. The literature is classified using a typology reflecting the orientations of service, pathology, disciplines, and the philosophy of education. The paper is global in reach, covering articles concerning countries in Europe, Asia Pacific, Latin America, and the Middle East. It offers recommendations to universities from the authors' home university perspective. The paper concludes with a discussion and reflections concerning what the literature and experiences suggest and ends with a brief research agenda.